2018
DOI: 10.20897/ejsteme/3871
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Design Challenges in Early Childhood Education: Effects on Student Cognition and Interest

Abstract: This mixed methods study is one of the first to evaluate the effects of the incorporation of dramatic inquiry, dance, visual arts and physical education into preK-3 science, technology, engineering and mathematics units on student conceptual understanding of technology and engineering. The study used data collected from over 200 student surveys and focus group interviews with 14 teachers. The use of integrated STEAM units supported significant improvement in 4 to 8 year old students' understanding of engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…In contrast to inquiry science learning which aims to build conceptual understanding (Hodson, 2014), STEAM learning needs to pay attention to elements of engineering and technology learning that aim to solve problems (Lottero-Perdue et al, 2016) so that EDP is a suitable approach to be applied in STEAM learning. Based on the study's results, it is known that STEAM EDP learning for early childhood can increase children's interest and understanding of the world of engineering and technology (Malone et al, 2018).…”
Section: B Discussionmentioning
confidence: 99%
“…In contrast to inquiry science learning which aims to build conceptual understanding (Hodson, 2014), STEAM learning needs to pay attention to elements of engineering and technology learning that aim to solve problems (Lottero-Perdue et al, 2016) so that EDP is a suitable approach to be applied in STEAM learning. Based on the study's results, it is known that STEAM EDP learning for early childhood can increase children's interest and understanding of the world of engineering and technology (Malone et al, 2018).…”
Section: B Discussionmentioning
confidence: 99%
“…SE content was explicitly targeted throughout the E 2 intervention, whereas technology content was only explicitly targeted on the first day of the intervention. Malone et al (2018) utilized the same measure and reported Cohen's d on this measure as 0.94, 0.85, 0.52, and 1.78 for kindergarten, first, second, and third grade levels, respectively. Calculating Cohen's d for the effects of this study revealed that the magnitude of the impact for all three grade levels was 1.15, 1.12, and 1.22, for kindergarten, first, and second grade, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Kajian terkait STEM secara umum masih berbasis pada level pendidikan dasar dan menengah, perhatian STEM di level PAUD masih minim (Park et al 2017). Apalagi konten terkait engineering di PAUD, konten terkait engineering baru dikaji oleh (Malone et al 2018;Malone, Irving, and Tiarani 2019;Pantoya, Hunt, and Aguirre-Munoz 2015;Bagiati et al 2010). Konten engineering perlu di PAUD perlu dikembangkan lebih mendalam karena dapat membantu perkembangan sains anak berkembang lebih optimal (Pawilen and Sumida 2009;Dubosarsky et al 2018).…”
Section: Pendahuluanunclassified
“…Pembelajaran STEM dalam bidang-bidang dipelajari dengan baik dan perlu menyediakan alat dan bahan yang tepat (Park, 2016). Engineering yang dasar dapat digunakan dan membantu dalam memecahkan masalah, mencari solusi, dan mengungkapkan gagasan atau pendapat (Malone, 2018). Proses mengidentifikasi dan memecahkan masalah dimana proses awal anakanak dalam mengkonstruksi dialam dan guru sebaiknya merancang proses kegiatan engineering agar anak memahami dan melakukan langkah-langkah kegiatan (Meeteran, dkk, 2010).…”
Section: Pengembangan Kemampuan Anakunclassified